2017
DOI: 10.5535/arm.2017.41.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the KAT6B Mutation via Diagnostic Exome Sequencing to Diagnose Say-Barber-Biesecker-Young-Simpson Syndrome in Three Generations of a Family

Abstract: Diagnostic exome sequencing (DES) is a powerful tool to analyze the pathogenic variants leading to development delay (DD) and intellectual disability (ID). Recently, heterozygous de novo mutation of the histone acetyltransferase encoding gene KAT6B has been recognized as causing a syndrome with congenital anomalies and intellectual disability, namely Say-Barber-Biesecker-Young-Simpson (SBBYS) syndrome. Here we report a case of SBBYS syndrome in a third generation Korean family affected with a missense mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In cases in which a given abnormality has not been detected or reported, its occurrence was taken as zero. Data were collated from reFs 136,137,139,142,144,147,149,[270][271][272][273] . RBS, Robert syndrome; RTS, Rubinstein-Taybi syndrome.…”
Section: Diencephalonmentioning
confidence: 99%
“…In cases in which a given abnormality has not been detected or reported, its occurrence was taken as zero. Data were collated from reFs 136,137,139,142,144,147,149,[270][271][272][273] . RBS, Robert syndrome; RTS, Rubinstein-Taybi syndrome.…”
Section: Diencephalonmentioning
confidence: 99%
“…While KAT6B disorders are inherited in an autosomal dominant manner, most individuals with a KAT6B disorder have had a de novo pathogenic variant including ours. Kim et al [16] reported the familial inherited mutation of the KAT6B variant (c.2292C>T, p.His767Tyr) causing relatively mild disease in three individuals with SBBYSS. In Korea, two cases have reported KAT6B mutation including GPS (NM_012330.3: c4543C>T, p.Gln1515Ter) and familial SBBYSS mentioned above [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [16] reported the familial inherited mutation of the KAT6B variant (c.2292C>T, p.His767Tyr) causing relatively mild disease in three individuals with SBBYSS. In Korea, two cases have reported KAT6B mutation including GPS (NM_012330.3: c4543C>T, p.Gln1515Ter) and familial SBBYSS mentioned above [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Although causative variants of SBBYSS are located distally to exon 18 of KAT6B, those of GPS are located more proximally to exon 18 [Zhang et al, 2020]. Recently, several reports have shown that KAT6B variants in exons more proximal to exon 18 can cause unique SBBYSS and GPS phenotypes [Clayton-Smith et al, 2011;Kim et al, 2017;Marangi et al, 2018;Zhang et al, 2020]. Here, we present a patient with global developmental delay, intellectual disability, autistic behavior, muscular hypotonia, facial dysmorphism, and seizures, but with a phenotype different from that of SBBYSS and GPS caused by a de novo heterozygous missense variant in exon 7 of KAT6B.…”
Section: Introductionmentioning
confidence: 99%